2017
DOI: 10.5588/ijtld.17.0023
|View full text |Cite
|
Sign up to set email alerts
|

Smoking behavior and beliefs about the impact of smoking on anti-tuberculosis treatment among health care workers

Abstract: SUMMARY SETTING Tuberculosis (TB) health care facilities throughout Georgia. OBJECTIVE To describe smoking behaviors among health care workers (HCWs) at TB facilities and determine HCWs’ knowledge and beliefs regarding the impact of tobacco use on anti-tuberculosis treatment. DESIGN Cross-sectional survey from May to December 2014 in Georgia. Adult HCWs (age ≥ 18 years) at TB facilities were eligible. We administered a 60-question anonymous survey about tobacco use and knowledge of the effect of smoking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…39,40 Training and supervision are a key requisite for integrating smoking cessation messaging into routine NTPs. 41,42 HCWs themselves may smoke and not recognize the importance of smoking cessation messages, particularly for TB patients. 30,41 In addition, even if HCWs agree with smoking cessation, they may not have adequate knowledge to provide tailored advice for TB patients.…”
Section: Practice Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 Training and supervision are a key requisite for integrating smoking cessation messaging into routine NTPs. 41,42 HCWs themselves may smoke and not recognize the importance of smoking cessation messages, particularly for TB patients. 30,41 In addition, even if HCWs agree with smoking cessation, they may not have adequate knowledge to provide tailored advice for TB patients.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…41,42 HCWs themselves may smoke and not recognize the importance of smoking cessation messages, particularly for TB patients. 30,41 In addition, even if HCWs agree with smoking cessation, they may not have adequate knowledge to provide tailored advice for TB patients. 30,41,42 For example, one study noted that TB nurses asked patients about smoking habits and gave advice 87% of the time, but did not provide TB-specific messaging that could increase the likelihood of quitting.…”
Section: Practice Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSM in this study reported cessation to be important; MSM in other lowresource settings also show interest in a broad range of cessation intervention supports . Unfortunately, doctors in many LMICs, such as China, infrequently offer cessation services and lack cessation resources (Berg, Nehl, Wang, Ding, He, Johnson, et al, 2014;Magee et al, 2017;Smith & Leggat, 2007). Indeed, one study of TB healthcare providers in Georgia indicated several barriers to providing smoking cessation support, including insufficient training in smoking cessation (Magee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, doctors in many LMICs, such as China, infrequently offer cessation services and lack cessation resources (Berg, Nehl, Wang, Ding, He, Johnson, et al, 2014;Magee et al, 2017;Smith & Leggat, 2007). Indeed, one study of TB healthcare providers in Georgia indicated several barriers to providing smoking cessation support, including insufficient training in smoking cessation (Magee et al, 2017). Perceived or enacted stigma among MSM (Costenbader et al, 2009) or PLWH (Hatzenbuehler et al, 2013) may also be barriers to seeking or receiving cessation services.…”
Section: Discussionmentioning
confidence: 99%